Expression of Hsp70 reveals significant differences between fin regeneration and inflammation in Paramisgurnus dabryanus. Issue 64 (May 2017) - Li, Li; Wang, Linlin; He, Jingya; Chang, Zhongjie
Abstract: Hsp70 is the most strongly induced in response to various cellular stresses and a good candidate for investigating its role in tissue injury. We firstly cloned full-length cDNA of hsp70 from Paramisgurnus dabryanus ( PdHsp70 ) by RACE method (GenBank:KP402408.1 ). Then regeneration and inflammation of fin were established by amputation and scratch respectively. Quantitative RT-PCR detected the PdHsp70 began to increase rapidly its expression at 1 days post amputation (dpa) and reached the peak at 2 dpa during fin regeneration. Its expression was also up-regulated at 2 days post scratch (dps) of inflammation but still significant weaker in comparison with it in regenerated fin at 2 dpa. Next, immunohistochemistry analysis of PdHsp70 showed that PdHsp70 located mainly in the deeper epidermis of regenerated fin and was stronger than its expression in the scratched inflammatory fin which was involved in whole epidermal. SDS-PAGE and Western blotting confirmed that the PdHsp70 protein expressed efficiently in Escherichia coli BL21. These findings have implied that PdHsp70 are implicated in different regulation of regeneration and inflammation in response to injury stimulation. During the regeneration, it is involved in the formation of wound epidermis by mediating cellular protection whereas it can modulate inflammatory by activating the innate immune response. Highlights: The full-length cDNA of PdHsp70 was cloned. A kind of fin wound inflammation condition separated from regeneration was built. The expression and distribution of PdHsp70 were different between regeneration and inflammation. The prokaryotic expression of PdHsp70 was analyzed by constructing recombinant plasmid.